“Propuesta de una guía práctica para la conformación legal y trámites de formalización de empresas en la ciudad de Loja” - Burneo Romero, Jaime Arturo (2024)
Bureaucratic procedures pose a challenge for business legalization, including for startups in the city of Loja. Although they do not completely prevent the process, these bureaucratic hurdles increase difficulties for entrepreneurs. Therefore, it is important to simplify the procedures and requirements needed to formalize a business. The general objective of the research was to develop and distribute a detailed practical guide for the legal formation and formalization processes for businesses in Loja, providing entrepreneurs and business owners with accurate and up-to-date information. The methodology encompassed a deductive study with a quantitative research approach, being non-experimental yet exploratory and descriptive, with a cross-sectional research design conducted through surveys of 204 entrepreneurs from Loja. Results indicated that these entrepreneurs face challenges in legalizing their businesses primarily due to three factors: lack of information on required documentation, complexity in understanding necessary requirements, and long waiting times in administrative processes. Entrepreneurs in Loja highlighted that more efficient formalization would require simplified procedures, greater access to clear, updated information, and faster administrative processes. The research concluded that Loja entrepreneurs encounter certain obstacles in formalizing their businesses, emphasizing the need for simplified, accessible, and up-to-date procedures, along with quicker, easier-to-understand processes. The practical guide is presented as an initial solution, aiming to encourage relevant institutions involved in business legalization to take action toward simplifying these procedures.